Strategy For The Development Of Independent Tourism Villages At The National Level In Belawa Tourism Village, Cirebon Regency - Ari Wibowo, Toni; Listiyati, Tia (Ann Publisher, 2025)
Background. Belawa tourism village is located in Lemahabang sub-district, which has tourism potential that can be developed to improve the welfare of the community, involving the community in the process of tourism activities. Purpose. The purpose of this activity is to provide an overview of the potential objects and tourist attractions owned by the Belawa tourism village. Method. This research activity is carried out through field research to obtain precise data on the research object through observation, as well as in-depth interviews, whose results will be described qualitatively. Result. Research. Inventory of potential tourist attractions based on tourist attractions, accessibility, amenities, human resources, tourism industry, and local community involvement. Conclusion. Belawa tourism village as one of the tourism destinations that has tourism potential that can be developed, so it is necessary to identify and develop strategies to increase the economy of the community by involving the local community